Pisonia calafia (Nyctaginaceae) species nova from the Baja California Peninsula, Mexico - León de la Luz, José Luis; Levin, Rachel A. (Instituto de Ecología, A.C., 2022)
Pisonia is a primarily American genus, distributed mainly in subtropical to tropical regions. In this paper a new species, Pisonia calafia, is described and documented. This species occurs as a small population on a coastal strand in the Cape Region of the Baja California Peninsula. The main characteristics that differentiate P. calafia from the rest of Pisonia is the lack of sulci and glands in the fruit. In addition to the new species description, we discuss the evolutionary affinities of this new taxon based on phylogenetic analysis of nrITS sequence data. The known population is limited to a few dozen individuals, now seriously endangered by the ongoing development of tourism projects.